Ulama and Umara Communication Patterns in Fostering Islamic Dayah Education in Aceh: Methods and Barriers - Zulfikar, Zulfikar; Lubis, Lahmuddin; Abdurrahman, Abdurrahman; Abdullah, Amiruddin (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This topic undoubtedly creates varied opinions of Islamic religious scholars regarding the communication methods used by the Aceh Islamic boarding school and Bireuen District so far, thus it's important to change attitudes and attitudes while communicating with Islamic academics.In order to avoid a gap between the ulama and the district, the Aceh dayah education office and the regency do not distinguish between dayah clerics in Bireuen Regency when communicating with them. To assess their needs and meet their leaders, the dayah education office should visit all dayah ualam in Bireuen Regency. Aceh and Bireuen District's dayah education offices must also build a mechanism to interact with Bireuen Regency's inner dayahs, some of which have never been visited.Based on the author's observations during interviews and direct observation of spaciousness, the researcher found several barriers to communication between the ulama and umara, such as not knowing the head of the service, the head of the elected dayah service did not understand about the dayah, the head of the service was not the choice of the dayah cleric, the head of the service was under the control of a certain group, or the head of the service was not elected. This prevents the dayah clergy and education administration from communicating for an undetermined duration. Until the education service's head is removed, clergy may teach dayah without official approval.The ulema needs to learn about the new dayah education office head's leadership style and communication style due to the contrasts between the two. Some dayah clerics care about the new service head, but others don't, therefore they take their time contacting or waiting for an invitation from the Aceh dayah education office and Bireuen Regency.